2009
DOI: 10.1007/s11284-009-0670-x
|View full text |Cite
|
Sign up to set email alerts
|

Size‐specific growth patterns and estimated longevity of the unionid mussel (Pronodularia japanensis)

Abstract: Despite the dwindling populations and an urgent need for conservation of unionid freshwater mussels in Japan, there are gaps in our understating of their fundamental ecology. This study examined size-dependent annual growth rates, elucidated size-specific intraannual growth patterns, and estimated age and longevity of P. japanensis individuals for two locally isolated populations in agricultural drainage channels. Annual growth rates of P. japanensis were strongly size-dependent, with growth rates being expone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 36 publications
2
20
0
Order By: Relevance
“…Factors that have been found to correlate with mussel growth and survival rates include, but are not limited to, substrate type and size (Hinch et al 1986;Liberty et al 2007), flows and sediment load (Beaty 1997;Zimmerman 2003;Jones et al 2005;Liberty et al 2007;Rypel et al 2008), toxicant exposure (Pandolfo et al 2010a), mussel density (Hanson et al 1988;Beaty 1997;Beaty and Neves 2004;Negishi and Kayaba 2009), food availability (Hanlon 2000), sampling frequency (Beaty 1997;Zimmerman 2003;Liberty et al 2007), maturity of larvae (Jones et al 2005), and temperature (Hanson et al 1988;Buddensiek 1995;Beaty 1997;Hanlon 2000;Zimmerman and Neves 2002;Zimmerman 2003;Liberty 2004;Hanlon and Neves 2006;Pandolfo et al 2010aPandolfo et al , 2010bNegishi and Kayaba 2010). These studies have helped define requirements for mussel propagation and culture by advancing understanding of factors affecting growth and survival and have shown that mussels are useful biological indicators of environmental change.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Factors that have been found to correlate with mussel growth and survival rates include, but are not limited to, substrate type and size (Hinch et al 1986;Liberty et al 2007), flows and sediment load (Beaty 1997;Zimmerman 2003;Jones et al 2005;Liberty et al 2007;Rypel et al 2008), toxicant exposure (Pandolfo et al 2010a), mussel density (Hanson et al 1988;Beaty 1997;Beaty and Neves 2004;Negishi and Kayaba 2009), food availability (Hanlon 2000), sampling frequency (Beaty 1997;Zimmerman 2003;Liberty et al 2007), maturity of larvae (Jones et al 2005), and temperature (Hanson et al 1988;Buddensiek 1995;Beaty 1997;Hanlon 2000;Zimmerman and Neves 2002;Zimmerman 2003;Liberty 2004;Hanlon and Neves 2006;Pandolfo et al 2010aPandolfo et al , 2010bNegishi and Kayaba 2010). These studies have helped define requirements for mussel propagation and culture by advancing understanding of factors affecting growth and survival and have shown that mussels are useful biological indicators of environmental change.…”
Section: Discussionmentioning
confidence: 99%
“…Due to their small size (<10-20 mm), juvenile mussels are difficult to detect in the wild, restricting field investigations to Downloaded by [Eastern Michigan University] at 12:55 09 October 2014 adult life stages and making it difficult to examine effects of temperature and other factors on early life stages (Negishi and Kayaba 2010). Though growth rates of juveniles from fieldbased studies are uncommon, researchers have begun to close this knowledge gap by utilizing laboratory-propagated juveniles for experimental studies, as we have done.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of these environmental characteristics and the combination of physiological, trophic, and reproductive patterns discussed above, five distribution models were found: 1. the greater species richness of native gastropods in permanent headwater streams, both stenochoric (A. wolfi) and widely distributed species (G. truncatula, R. balthica, P. metidjensis), is also related to ecological factors linked to the low diversity and abundance of fish in these streams and, thus, low predation pressure (Wellborn et al, 1996;Doadrio, 2001;Pilliod & Peterson, 2001); 2. the habitat preferences of euryhaline native gastropod species (M. emiliana, P. ulvae and M. myosotis) responds, mainly, to physiological adaptations to high water conductivity levels, together with a variety of tidal habitat requirements (Berger & Gorbushin, 2001;Piscart et al, 2005;Cardoso et al, 2007), which also means that, unlike the headwater communities, estuarine gastropod communities have a more simple organization based on a low number of species resistant to sudden, large changes in conductivity (Piscart et al, 2006); 3. to maximize their reproduction and growth, naiads (bivalves of the genera Anodonta, Unio and Potomida) select permanent lowland water courses close to the central axis of the Guadiana River, with moderate slopes and muddy substrate (high turbidity) (Morris & Corkum, 1999;Negishi & Kayaba, 2010); 4. both genus Pisidium bivalve species occupy steep slopes-streams, located at great distances from the Guadiana River axis, probably reflecting their preference for permanent headwater environments (Dussart, 1976;Holopainen, 1980;Gallardo et al, 1994); and 5. the distribution of the eurychoric native gastropod species A. cf. fluviatilis reveals their opportunistic behaviour; they colonize highly variable Mediterranean environments (Gallardo et al, 1994;Kefford & Nugegoda, 2005) and so can be found in headwater, lowland, and tidal temporary or permanent streams (Gallardo et al, 1994;Bennike & Lemke, 2001;Kefford & Nugegoda, 2005;Kefford et al, 2007;Zalizniak et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…First, we know that rates of biomass accumulation in mussels decrease with size: smaller mussels gain more mass per unit time than larger individuals (e.g., Sukhotin et al 2002, Negishi andKayaba 2010). Second, differently sized mussels rely on overlapping (if not completely equivalent) resource pools: according to Widdows et al (1979), adult mussels are non-selective filter feeders whose gills retain all particles larger than 5 lm.…”
Section: Spatial Decoupling Of Adult and Recruit Abundancesmentioning
confidence: 99%